The Perception of Business Ethics in the Public and Private Sector: A study of Portuguese Social Representations - Pais, Leonor (2022)
Over the years, people have become more aware of how companies influence their lives, communities, and the environment. This influence has led to a growing interest and a vast and distinct literature in business ethics. Despite the diversity of themes concerning business ethics, the literature concerning social representations of business ethics in public and private sectors is scarce. This article explores the differences and similarities of Portuguese social representation between two business sectors (public and private). A Free Evocations Test was applied for that purpose, and the answers were analyzed using EVOC software. The results interpreted based on Abric’s Theory of the Central Nucleus showed a central core organized around the concept of ‘respect’ in the two business sectors and ‘responsibility’, ‘honesty’, ‘justice’, ‘code of conduct’, ‘confidentiality’ and ‘ethic’ in the central core of the private sector.